Profit Planning Case Study Using Break Event Point Analysis at the Lucky Fried Chicken MSME in Blitar Regency: Studi Kasus Perencanaan Laba Menggunakan Analisis Break Event Point Pada UMKM Ayam Geprek Lucky Di Kabupaten Blitar - Linda Puspita Dewi; Dwi Anggarani; Khojanah Hasan (DPD Jatim Perkumpulan Dosen Indonesia Semesta, 2026)
This case study is based on the situation of culinary MSMEs facing fluctuations in raw material prices and changes in market demand, which affect profit stability. This situation requires financial planning based on quantitative analysis. The Break Even Point (BEP) is used to determine minimum sales limits and profit targets. The case study was conducted on the Ayam Geprek Lucky MSME (Micro, Small, and Medium Enterprises) in Blitar Regency through interviews, observations, and documentation. The results indicate that fixed and variable costs influence business performance. The BEP has proven effective as a basis for pricing, production planning, and cost control. Practically, the study results provide an applicable model for MSMEs in managing cost structures, setting sales targets, and developing contribution margin-based pricing strategies.